Influence Of Accounting Understanding and Internal Control On The Quality Of Financial Statements - Wahyuni Saleh; Andi Riska Andreani (Bongaya Journal for Research in Accounting (BJRA), 2022)
This study aims to examine the effect of understanding accounting and internal control on the quality of financial statements. The data in this study were obtained from business actors, namely the owners of stands at Karebosi Link Makassar City who were the respondents. This study uses primary data obtained directly from original sources not through intermediaries and collected by researchers to answer research questions by giving questionnaires to 39 respondents. The sampling method in this study used the purposive sampling method, namely the technique of determining the sample with certain criteria or considerations. Test the validity and reliability of the data to determine whether the indicators of the questionnaire are valid and reliable. The data analysis method used is multiple regression analysis, coefficient of determination test (r2) and simultaneous test (f). The results of this study indicate that partially and simultaneously Accounting Understanding has a positive and significant influence on the Quality of Financial Statements survey on stand owners at Karebosi Link Makassar and partially and simultaneously Internal Control has a positive and significant influence on the Quality of Financial Statements survey on stand owners at Karebosi Link. Makassar. Keywords: Understanding of Accounting; Internal Control; Quality of Financial Statements